Lexical proximity of a Xri corpus to Khoekhoegowab - Wilfred H.G Haacke (LibraryPress@UF, 2019)
The present paper examines a corpus of some 1 130 Xri concepts collected by Jan Snyman (UNISA) in the early 1970s. This collection is by far the largest corpus of vocabulary of self-declared "Griekwa" speakers available, and is unlikely to be surpassed in future, as the language is moribund. 1096 concepts of this Xri corpus are compared dialectometrically to the equivalents in Namibian Khoekhoegowab (Khoekhoe, formerly “Nama/Damara”).  According to this method the rate of cognation between the Xri corpus and its Khoekhoe equivalents is 69% and consequently sets Xri aside as a lect distinct from Khoekhoegowab. While the entire word list is provided in an appendix, distinctive correspondences of the segmental phonology are discussed.  The crucial question whether Xri had a three-tone system like !Ora or a four-tone system like Khoekhoegowab cannot be investigated reliably because of the absence of tonal data for Xri. The fact, however, that Xri (like !Ora) distinguishes certain voiced and voiceless consonants permits the conclusion that it too had a pre-tonogenetic system where voicing still is distinctive and – assumedly - has not caused tonal depression as in Khoekhoegowab.   Although no dialectomeric comparison of !Ora and Xri lexicon has been undertaken, certain systematic phonological contrasts between these two lects set Xri aside also from !Ora as a distinct lect in this dialect continuum